Mother to child transmission of HIV in Plateau State, Nigeria: Case-based surveillance of the HIV infected HIV-exposed infants - Emmanuel O. Osayi; Sarah C. Blake; Kelechi Ngwoke; Catherine Pius; Tolulope Afolaranmi; Atiene S. Sagay (PLoS ONE, 2026)
Introduction HIV infection among children is predominantly due to perinatal transmission. The timing of HIV-related symptoms in perinatally infected children reveals how quickly the disease progresses and helps predict prognosis. This study used case-based surveillance to examine treatment outcomes and disease progression among HIV-infected, HIV-exposed infants in Plateau State, Nigeria. Method This is a retrospective cohort study using a case-based surveillance approach. The data of HIV-exposed infants enrolled between 1 st October 2018 and 30 th September 2022, who had confirmed positive DNA PCR results and commenced antiretroviral therapy (ART), were sampled via a cluster sampling method. Participants were followed up for 6 months to 5 years post-ART initiation. Disease progression, treatment mortality, and loss outcomes were assessed with respect to age at follow-up. Results A total of 57 infants were included in the study, drawn from 15 health facilities across the three senatorial districts of Plateau State, Nigeria. The female-to-male ratio was approximately 1:1 (29:28), with a mean age of 0.7 years (8.9 months) ± 0.7 years at ART initiation. By the end of the follow-up period, 70% (40/57) of the infants had favorable treatment outcomes, with 87.5% achieving viral suppression. The remaining 29.8% (17/57) experienced treatment mortality or losses (TX_ML): 47.1% (8/17) died, 29.4% (5/17) transferred out, 17.6% (3/17) discontinued treatment, and 5.9% (1/17) interrupted treatment. Among those with mortality outcomes, 75% died before the age of two years, while 25% survived beyond two years, with some reaching up to their fourth birthday. Mortality was unevenly distributed across local government areas (LGAs), with the highest rates recorded in Mangu LGA (37.5%), followed by Shendam LGA (25%), and the remaining 37.5% shared equally among Pankshin, Langtang North, and Jos North. Conclusion This study revealed disparities in TX_ML outcomes across senatorial districts, with higher treatment mortality in the Southern and Central districts compared to the Northern district. These findings highlight the need to design targeted, context-specific interventions to improve survival and treatment outcomes among perinatally HIV-infected children and further research to identify the contributing factors.